Metabolic oxidative stress elicited by the copper(II) complex [Cu(isaepy)2] triggers apoptosis in SH-SY5Y cells through the induction of the AMP-activated protein kinase/p38MAPK/p53 signalling axis: evidence for a combined use with 3-bromopyruvate in neuroblastoma treatment - Giuseppe Filomeni; Simone Cardaci; Ana Maria da Costa Ferreira; Giuseppe Rotilio; Maria Rosa Ciriolo (2011)
We have demonstrated previously that the complex bis[(2-oxindol-3-ylimino)-2-(2-aminoethyl)pyridine-N,N']copper(II), named [Cu(isaepy)(2)], induces AMPK (AMP-activated protein kinase)-dependent/p53-mediated apoptosis in tumour cells by targeting mitochondria. In the present study, we found that p38(MAPK) (p38 mitogen-activated protein kinase) is the molecular link in the phosphorylation cascade connecting AMPK to p53. Transfection of SH-SY5Y cells with a dominant-negative mutant of AMPK resulted in a decrease in apoptosis and a significant reduction in phospho-active p38(MAPK) and p53. Similarly, reverse genetics of p38(MAPK) yielded a reduction in p53 and a decrease in the extent of apoptosis, confirming an exclusive hierarchy of activation that proceeds via AMPK/p38(MAPK)/p53. Fuel supplies counteracted [Cu(isaepy)(2)]-induced apoptosis and AMPK/p38(MAPK)/p53 activation, with glucose being the most effective, suggesting a role for energetic imbalance in [Cu(isaepy)(2)] toxicity. Co-administration of 3BrPA (3-bromopyruvate), a well-known inhibitor of glycolysis, and succinate dehydrogenase, enhanced apoptosis and AMPK/p38(MAPK)/p53 signalling pathway activation. Under these conditions, no toxic effect was observed in SOD (superoxide dismutase)-overexpressing SH-SY5Y cells or in PCNs (primary cortical neurons), which are, conversely, sensitized to the combined treatment with [Cu(isaepy)(2)] and 3BrPA only if grown in low-glucose medium or incubated with the glucose-6-phosphate dehydrogenase inhibitor dehydroepiandrosterone. Overall, the results suggest that NADPH deriving from the pentose phosphate pathway contributes to PCN resistance to [Cu(isaepy)(2)] toxicity and propose its employment in combination with 3BrPA as possible tool for cancer treatment.